Penurunan Konsentrasi Logam Ni Pada Limbah Cair Elektroplating Dengan Bionanomaterial Chitosan Dari Limbah Cangkang Kulit Udang - Juniwarnis Juniwarnis; Shinta Elystia; Zultiniar Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Chitosan is one of the solutions in reducing heavy metal contamination inelectroplating industrial wastewater. Bionanomaterial chitosan has better ability because it has a specific surface area and nano-scale particle size. This research uses bionanomaterial chitosan to remove Ni from electroplating wastewater. This study aims to determine the effect of bionanomaterial chitosan concentration andstirring time in removing Ni in electroplating wastewater with variation ofconcentrations of 4000; 8000; 12000; and 16000 mg/L and stirring times of 30, 60 and 90 minutes using jar test. The initial concentration of Ni in electroplating wastewater was 2,025 mg/L. After the adsorption process, the highest efficiency value for Ni was 98,667 % at bionanomateial chitosan concentration of 8000 mg/Land a stirring time of 30 minutes.Keywords: Bionanomaterial Chitosan, Adsorption, Ni, Electroplating Waste Water.